Дијагностички и хируршки особености на плеоморфен аденом на паротидната жлезда: евалуација на ризик факторите за рецидив и морбидитет на фацијалниот нерв - Касами, Недим (Стоматолошки факултет, УКИМ, Скопје, 2021)
Pleomorphic adenoma is the most frequent benign tumor of the salivary glands. It is characterized by a tendency to recur, which is determined by the biological characteristics of the tumor as well as the mode of its treatment. Fine needle aspiration cytology (FNAC) for diagnosis of a parotid gland tumor is widely used but its sensitivity is low and non-diagnostic rate is relatively high. MRI provides information on the exact localization and extent of the lesion, also in the deep lobe and the parapharyngeal space. MRI allows detecting perineural spread, bone invasion and meningeal infiltration. Like for extended diagnostics for benign tumors, CT should be used for further staging if MRI is not available or contraindicated. Recurrence of the tumor is associated with a high risk of postoperative facial palsy, risk of subsequent recurrence and an increased risk of malignant transformation. Among the factors, the most important are: incomplete excision, intraoperative capsule rupture, myxoid subtype, presence of the satellite nodules and the experience of the surgeon . The possible factors are: the female sex, young age, location and size of the tumor, and the duration of the tumor growth. The technique of tumor enucleation of pleomorphic adenoma carries a high risk of recurrence and should be replaced by parotidectomy. The aims of the study were evaluation and correlations of histological properties of tumor (it’s size, location, subtype), mode of treatment and rate of recurrence, to compare the incidence of postoperative facial morbidity related to these variables, by using clinical- neurophysiological assessment of facial nerve function post-operatively. Also, we sought to evaluate additional information about risk factors for postoperative facial weakness in parotid tumor surgery, particularly focusing on the duration of the tumor growth, subtype, size and subsite. This study includes retrospective combined with prospective and descriptive clinical study cases of overall 77 patients with benign tumor ( PA ), treated in our clinic in a period from 2016 to 2020. Tumor subsites were stratified based on their anatomical location being in superficial or in the deep lobe of the gland. The values of the size and the subtype of the tumor were obtained from the pathohistological findings after the surgery, comparing the results with the preoperative assessment with CT or MRI values. Clinical assessment was based on House–Brackmann scale (H–B), postoperatively and the neurophysiological diagnostic measurement which included surface mimetic muscle electromyography (S- EMG), and blink-reflex (BR), comparing the affected side with the non-affected one, performed by specialist neurologist. Multivariable logistic regression analyses were conducted to identify risk factors for the recurrence, and postoperative facial weakness. A descriptive, inferential and binary logistic regression analysis were performed for the variables facial nerve dysfunction, tumor size, location and it`s subtype. A statistically significant relationship was found between the appearance of facial paresis and tumor location in the superficial lobe, size and myxoid subtype. Neurophysiological studies detected clinically silent facial nerve neuropathy of mandibular marginal branch in postoperative period. S- EMG, allows for the evaluation of face muscles reinnervation and facial nerve regeneration. Mainly grade I of H–B was recorded post-operatively in patients with small benign tumors located in superficial lobes. H–B and EMG results revealed positive correlations between the type of tumor and surgery with facial nerve function. The commonest complications after parotidectomy are temporary or permanent facial palsy and Frey’s syndrome. Tumor location in the parotid superficial lobe upper area, size and myxoid subtype are risk factors for recurence and can worsen facial paresis. The knowledge of these complications is relevant for patient´s counseling and to achieve better long-term outcomes. The best means of reducing iatrogenic facial nerve injury in parotid surgery remains a keen understanding of the anatomy coupled with a gentle technique. This study result may provide background data in a future prospective study and up-to-date information for patient counseling.
Diagnostic and surgical features of pleomorphic adenoma of the parotid gland: evaluation of risk factors for recurence and facial nerve morbidity
Докторска дисертација одбранета во 2021 година на Стоматолошкиот факултет во Скопје, под менторство на проф. д–р Владимир Поповски.
Keywords: Pleomorphic adenoma, risk factors, superficial parotidectomy, facial nerve palsy, House–Brackmann scale, electromyography, Blink reflex